Construction of immunotherapy-related prognostic gene signature and small molecule drug prediction for cutaneous melanoma - Xing, Jiahua; Jia, Ziqi; Li, Yan; Han, Yan (Frontiers in Oncology, 2022)
Background: Cutaneous melanoma (CM), a kind of skin cancer with a high rate of advanced mortality, exhibits a wide variety of driver and transmitter gene alterations in the immunological tumor microenvironment (TME) associated with tumor cell survival and proliferation. Methods: We analyzed the immunological infiltration of TME cells in normal and malignant tissues using 469 CM and 556 normal skin samples. We used a single sample gene set enrichment assay (ssGSEA) to quantify the relative abundance of 28 cells, developed a riskScore prognostic model using the LASSO COX regression model, and performed small molecule drug screening and molecular docking validation, which was finally validated using qRT-PCR and IHC. Results: We developed a prognosis model around seven essential protective genes for the first time, dramatically elevated in tumor tissues, as did immune cell infiltration. The results of multivariate Cox regression demonstrated that riskScore is an independent and robust prognostic indicator, and its predictive usefulness in immunotherapy was verified. Additionally, we identified Gabapentin as a possible small molecule therapeutic for CM. Conclusions: A riskScore model was developed in this work to analyze patient prognosis, TME cell infiltration features, and treatment responsiveness. The development of this model aid in predicting patient response to immunotherapy, but it also has significant implications for the development of novel immunotherapeutic agents and the promotion of tailored treatment regimens.